Meliponitourism in the Philippines: Integrating stingless bee keeping and sustainable tourism for community development and biodiversity conservation - Amelia Nicolas (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2025)
Meliponitourism, the integration of stingless beekeeping with sustainable tourism, is an emerging niche within ecotourism that combines biodiversity conservation, cultural heritage, and community livelihood enhancement. While countries such as Brazil, Malaysia, Indonesia, and Australia have developed established models, the concept remains relatively new in the Philippines. This study employs a case-based approach to examine Philippine meliponitourism initiatives, focusing on their ecological foundations, socio-economic contributions, and development challenges. Data were gathered from peer-reviewed literature, institutional reports, and indigenous knowledge systems, with triangulation ensuring reliability and breadth of perspectives. Findings show that stingless bees (Tetragonula spp.) support both agricultural productivity and unique tourism offerings through high-value products such as pot-honey, pot-pollen, and propolis. Philippine case examples—including research-led projects by CBSUA and UPLB, community ventures such as Balay Buhay sa Uma Bee Farm, and indigenous practices of the Ibaloi, Aeta-Tabangnon, and Higaonon–demonstrate pathways by which meliponitourism can advance income diversification, women and youth empowerment, and pollinator-friendly conservation. However, challenges remain, particularly regarding product certification, policy integration, and technical capacity. Comparative insights from global models underscore the importance of institutional support, diversified product development, and participation in international networks. The study concludes that with enabling policies, inclusive community participation, and research-driven innovation, meliponitourism in the Philippines can evolve into a triple-win strategy that advances biodiversity conservation, strengthens rural livelihoods, and fosters sustainable tourism innovation.